Konsep Keuntungan Maksimal Sebagai Alasan Filipina Menggandeng Tiongkok pada Masa Pandemi COVID-19 - Evita Christiana (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2022)
Relations between the Philippines and China are filled with conflict and cooperation. The conflict between the two countries can be seen from the conflict in the South China Sea, while the cooperation between the Philippines and China can be seen in the form of investment, loans, and others. With these dynamics, the author then finds an anomaly related to why the Philippines, which is in conflict with China in the South China Sea still wants to cooperate with China during the pandemic of COVID-19. Through this research, the author aims to find out the reasons behind the Philippines' desire to cooperate. The author then argues that the cooperation happens because of the material benefits that the Philippines has received and the benefit of social relations. In doing this research, the author uses rational choice theory from a journal written by Linda K George. By using rational choice theory, the author will further review what choices the Philippines faces so that it prefers to cooperate with China.